2017
DOI: 10.1007/978-1-4939-7315-6_4
|View full text |Cite
|
Sign up to set email alerts
|

A Brief History of Promoter Development for Use in Transgenic Maize Applications

Abstract: Promoters regulate gene expression, and are essential biotechnology tools. Since its introduction in the mid-1990s, biotechnology has greatly enhanced maize productivity primarily through the development of insect control and herbicide tolerance traits. Additional biotechnology applications include improving seed nutrient composition, industrial protein production, therapeutic production, disease resistance, abiotic stress resistance, and yield enhancement. Biotechnology has also greatly expanded basic researc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 181 publications
1
20
0
Order By: Relevance
“…Such comparison has not been previously carried out on potato. The results presented here are generally in agreement with comparable studies performed on various species involved CaMV 35S promoter and plant-derived promoters of polyubiquitin genes [ 3 , 6 , 8 , 9 , 43 ]. According to the presented data, the constitutive promoters provided a higher level of gusA expression in leaves than in the tubers of potato.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Such comparison has not been previously carried out on potato. The results presented here are generally in agreement with comparable studies performed on various species involved CaMV 35S promoter and plant-derived promoters of polyubiquitin genes [ 3 , 6 , 8 , 9 , 43 ]. According to the presented data, the constitutive promoters provided a higher level of gusA expression in leaves than in the tubers of potato.…”
Section: Discussionsupporting
confidence: 91%
“…The use of a range of plant-derived promoters also contributes to the successful multi-gene transformation, which is aimed at the production of plants with stacked traits or at engineering metabolic pathways by simultaneous introduction and expression of several genes. It is highly recommended to drive introduced sequences under different promoters in order to avoid accidental gene silencing due to the homology of repetitious promoters [ 3 , 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Among other things, this has led to enhanced use of similar, or related promoters, such as the figwort mosaic virus 34S promoter (FMV 34S) 87,88 . It was also found that in monocots, such as rice and corn, the CaMV 35S is not as active as it is in dicots, leading researchers to switch to, e.g., the later discovered rice actin 1 or maize Ubi-1 promoters [89][90][91][92] . So even though the switch is happening at a slower pace in applied agriculture than it is in academia, the variety of promoters used is steadily increasing also in this area.…”
Section: The Camv 35s Promoter Today (2000-today)mentioning
confidence: 99%
“…The first is the classical breeding, that involves the sexual crossbreeding between plants of the same species or other closely related containing the characteristics of interest, such as drought tolerance (Beyene et al, 2016). The second strategy of plant breeding is based on transgenic techniques, for instance obtaining transgenic maize with improved drought tolerance (Nuccio, 2018). A third alternative, explored by this work, is the treatment with several molecules to mitigate the effects of stress in the plant.…”
Section: Introductionmentioning
confidence: 99%